Examining potential overlap of DSM-5 PTSD criteria D and E. (30th December 2016) - Franklin, C. Laurel; Walton, Jessica L.; Cuccurullo, Lisa-Ann; Raines, Amanda; Ball, Jaqueline; Vaught, Amanda; Chambliss, Jessica L.; Maieritsch, Kelly P.
Abstract: The Diagnostic and Statistical Manual, Fifth Edition-5 ( DSM-5 ) has adopted a four-factor symptom model for Posttraumatic Stress Disorder (PTSD) that includes new symptom additions in criterion D (D2, D3, D4), negative alterations in cognition and mood. This article examines potential overlapping endorsement of these symptoms amongst one another and with the behavioral symptoms within PTSD criterion E (E1 and E3; alterations in arousal and reactivity), through the lenses of cognitive-behavioral theory. Responses of veteran participants ( N =320) completing the PTSD Checklist-5 were used to determine overlap in symptom reporting. We conducted a series of direct logistic regressions to determine the predictive ability of meeting the criterion D or E symptoms based on endorsement of the target D symptoms (D2, D3, D4). Results suggest that the new cognitive and emotional symptoms of criterion D have significant overlapping content, and that thought-related symptoms are often endorsed in conjunction with their behavioral counterpoint (D2/E3; D4/E1). Our results suggest that DSM-5 criterion D symptoms may not be central to the diagnostic structure of PTSD. These symptoms add complexity and difficulty to diagnosing PTSD without adding much unique content. Highlights: Newly added PTSD Criterion D symptoms are endorsed in conjunction with each other. PTSD Criterion D symptoms share a considerable amount of variance. Most veterans met Criterion D threshold when the new symptoms were removed from the symptom count. The addition of D2, D3, & D4 may not be central to the diagnosis.